Muslim Identity in India and Pakistan - Shah, Muhammad Iqbal (South Asian Journal of Religion and Philosophy (SAJRP), 2023)
Allama Iqbal (d. 1938) lamented the backwardness of his own contemporary Muslim society. Sir Sayyid Ahmad Khan (d. 1898) had also seen the need for Muslims of his time to become aware of their culture and identity as Muslims. Both Iqbal and Ahmad Khan were aware of the positive as well as the negative influence of the British and the Hindu cultures on their own Muslim cultural identity. They realised that Muslims needed to become aware of their cultural legacy so as to recover an awareness of their own Muslim cultural values. Furthermore, both of these Muslim leaders saw education as the key to maintaining and transmitting the values of Islam to subsequent generations. Without education, the next generation would lose this sacred legacy. This article presents the basic elements of Allama Iqbal’s philosophy of education. The author explains the notion of khudi, which was Iqbal’s term for one’s own self-identity. Iqbal’s philosophy of education gives Muslims a framework by which to transmit their culture and identity to subsequent generations.